Comparative experimental study on mechanical mechanism of combined arches in large section tunnels. (May 2020) - Wang, Q.; Xin, Z.X.; Jiang, B.; Sun, H.B.; Xiao, Y.C.; Bian, W.H.; Li, L.N.
Abstract: The large section tunnel support is facing tremendous challenges. They are large in span and poor in self-stability of surrounding rocks. Traditional I-steel arches are easily subject to buckling failure. As a result, safety accidents always occur, such as the failure of supporting system and the collapse of tunnels. To solve the problems, a new support technology of confined concrete and corresponding arches are invented. With high strength and rigidity, it can effectively control the deformation of surrounding rocks on large section tunnels. To clarify the bearing capacity and failure mechanism of the new arch, a mechanical testing system for the combined arches in large section tunnels is developed. Comparative tests were carried out on the mechanical mechanism of the combined arches of confined concrete and traditional I-steel. The tests took Longding Tunnel, one of the largest city road tunnels in China, as engineering background. In the test, the following results were found. The in-plane flexural buckling occurred on the vault of the combined I-steel arch first, and then out-plane flexural-torsional buckling occurred on the hance and bottom of the arch. It resulted in the overall loss of its bearing capacity and the entire arch being flattened. In the other hand, the confined concrete combined arch showed no severe deformation; its bearing capacity was 2.63 times that of the I-steel arch; and its average rigidity at the coordinated bearing stage is 2.51 times that of the I-steel arch. It is superior in bearing capacity and stability to the I-steel arch. Based on the experimental research conclusions, the engineering suggestions are put forward for the application of the confined concrete support technology in tunnels and the field application was carried out. The control effect is excellent on surrounding rocks. The results can provide a reference for the future research and design in this field.